The Effect of Work-Life Balance, Employee Engagement and Training on Job Satisfaction and Employee Performance - Ni Nyoman Sawitri (Greenation Research & Yayasan Global Resarch National, 2024)
The article on the influence of work-life balance, and employee engagement training on job satisfaction and employee performance is a scientific literature review article within the scope of human resource management science. This article aims to create a hypothesis regarding the relationship between factors, which can then be used for further research in the field of human resource management. Descriptive qualitative research methodology was used in this research. The data used in this research comes from previous research which is still relevant to this research. Data was obtained from reputable academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The results of this research are as follows: 1) Work-life balance influences job satisfaction; 2) Employee engagement influences job satisfaction; 3) Training influences job satisfaction; 4) Work-life balance influences employee performance; 5) Employee engagement influences employee performance; 6) Training influences employee performance; and 7) Job satisfaction influences employee performance.